Countermovement push-up test to assess the upper extremity force-time characteristics in swimmers during a macrocycle - Öztürk, F.; Ünver, E.; Özçadirci, A.; Cinemre, S. A.; Kinikli, G. I. (PLOS ONE, 2023)
Although it is known that swimming training can improve upper extremity performance, the force-time characteristics of the upper extremity during different training periods are not well understood. The objective of this study was to measure changes in the force-time characteristics of the upper extremity of young swimmers during different training periods within a season. Seventeen young swimmers, comprising 5 males (age: 15.4 ± 0.54 years); 12 females (16.4 ± 2.6 years) participated in this study. They were tested at four experimental test time points: baseline (E1), post-general preparation (E2), post-specific preparation (E3), and taper season (E4). The countermovement push-up test was performed using a force plate to measure force time parameters. Differences in force, time, velocity and impulse parameters were evaluated between the different periods. The study found that vertical take off velocity significantly increased across the assessed periods (F = 11.79; p = .001; Eta2 = .424), with significant increases from E1 to E2 (p < .001) and from E3 to E4 (p = .016). Flight Time also significantly increased across the assessed periods (F = 11.79; p = .001; Eta2 = .424), with significant increases from E1 to E2 (p < .001), from E1 to E4(p = .001), and from E3 to E4 (p = .005). The Force Impulse significantly increased throughout the assessed periods (F = 5.84; p = .012; Eta2 = .267), with significant increases from E1 to E2, (p = .006), from E1 to E3 (p = .016), and from E1 to E4 (p = .003). As this study shows, periods of increased training intensity can affect athletic progression, even though training aims to improve strength, speed, and performance. While some practical aspects such as strength, flight time, and impulse parameters may change during a macrocycle, the countermovement push-up test can provide trainers with an alternative and convenient way to monitor anaerobic force, speed, and performance, as well as measure explosive force-time performance in the upper body.